Socio-religious behavior on consumption pattern during Israel and Palestine conflict in Muslim society - Airlangga PH, Ahmad Rahmatullah; Saputri, Widya Ajeng; Nurhakim, Putri Rahmah (Yayasan Irwan Abdullah Cendekia, 2023)
The changes in consuption patterns triggered by the Israeli-Palestinian conflict and the pro-Israel boycott movement in Indonesia are important since they show the influence of socio-religious values on cunsumers behavior and the resulting impacts on companies and the workforce. Previous studies primarily focused on analyzing the causes and implications of the conflict, and paid insufficient attention to the socio-religious behavior perspective in changing consumption patterns. This study includes boycott actions, the social and religious characteristics of both pro and con movements, and the involvement of state institutions in responding to the Israeli-Palestinian conflict. The desk research method is used by collecting data through digital media analysis, including online news, social media, and library research. The findings of this study include the internalization of social religious values as a driving force for boycott actions, moral considerations influencing the defense of opinions in society, and the involvement of major powers in strenghtening the boycott movement. The uniqueness of this study lies in its in-depth approach to religious social behavior in the context of changing consumption patterns amidst armed conflict.